Seismic Analysis of a Post Tensioned Slab as Per Indian Design Code Using Etabs - Akhalesh Kumar Patel; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
In building construction, post tensioning permits bigger clear ranges, more slender slabs, less bars and increasingly slim components. Post tensioning is the arrangement of decision for stopping structures since it permits a high level of adaptability in the segment format, range lengths and incline design. More slender slab implies less concrete is required. As the floor framework assumes a significant job in the general expense of a building, a post tensioned floor framework is created which lessens the ideal opportunity for the construction and by and large cost. This project deals with comparative analysis on Flat slab and Post tensioned slab considering parameters as storey displacement in X and Y Direction, Bending moment in X and Y Direction and Storey drift. A G+15 storey was considered for the analysis and the modelling and performance of the structure was registered using analytical applications Csi ETABS and SAFE. Seismic analysis was conducted as per defined IS codes. PT slabs provide proper stability and appearance to the structure which is capable of resisting lateral loads with decreasing the dead loads generating due to heavy sections and members.